Improving sulfur tolerance of Ni-YSZ anodes of solid oxide fuel cells by optimization of microstructure and operating conditions. (14th June 2018) - Mehran, Muhammad Taqi; Khan, Muhammad Zubair; Lee, Seung-Bok; Lim, Tak-Hyoung; Park, Sam; Song, Rak-Hyun
Abstract: In this study, we propose an improvement in the sulfur tolerance of nickel-yttria stabilized zirconia (Ni-YSZ) anodes for solid oxide fuel cells (SOFCs) by simultaneously employing optimized operating conditions and microstructural modifications. An electrolyte supported SOFC is operated at 20 ppm H2 S impurity at 750 °C for 20 h degradation and 10 h recovery test. The current cycles with a higher amplitude and small pulse time during the constant current operation are beneficial for the mitigation of sulfur poisoning. The effect of humidity on the sulfur degradation of Ni-YSZ anode is also studied. The synergetic effect of microstructure modification and current cycling conditions improves the sulfur tolerance of Ni-YSZ anode. It has been found that, when an anode with a modified microstructure by infiltrated CeO2 and Yb2 O3 nanoparticles is operated on 20 ppm H2 S poisoned gas at 10% relative humidity and the optimum pulsed current cycling conditions, about 7 times less degradation of the SOFC performance is observed. This study shows that at lower H2 S concentration, a stable operation of a SOFC with minimum degradation can be achieved with the combination of optimization of operating conditions and modification of the anode microstructure. Graphical abstract: Highlights: Sulfur tolerance of Ni-YSZ anodes improved by a novel method. Pulsed current cycles at specific intervals regenerates sulfur poisoned Ni in anode. Uniform surface modification of anode by infiltration of CeO2 Yb2 O3 nano-particles. Optimized conditions show 7 times improvement in sulfur tolerance of Ni-YSZ anodes.